Are there mountain xerphytes in the mountains of South Siberia? - Volkov, Igor V. (Arid ecosystems)
The regularities of biomorphological, ecological, and species differentiation of phytocenoses in the most arid southeastern sector of the Altai Republic reflect a tendency towards the local formation f a complete type of arid vertical zoning. This is typical for arid mountains of Central Asia and includes the following belts (from bottom to top): (1) dwarf shrub deserts, (2) communities of thorn cushion plants (mountain xerophytes), (3) high-mountain steppes, and (4) cryophyte cushion plant formations. The relatively wide spread of this zoning type (in areas with sufficient height of the mountains), including belts of thorn cushion plants and cryophyte cushion plant formations, requires the revision of traditional botanical-geographical concepts in order to increase the diversity of higher vegetation syntaxa and orobiomes both in the Southeastern Altai and in the mountains of South Siberia in general.